COPROLOGICAL PREVALENCE AND THE INTENSITY OF GASTROINTESTINAL NEMATODES INFECTION IN WORKING EQUINES, EAST AZERBAIJAN OF IRAN - A. Imani-Baran; J. Abdollahi; H. Akbari; A. Raafat (Journal of Animal and Plant Sciences, 2019)
This study aimed to determine the prevalence and intensity of GI nematodes, relationship between the prevalence and intensity of GI nematodes with intrinsic variables (age, gender and species) and species diversity of GI nematodes in working equines in the northwest of Iran from November 2016 to March 2017. A total of 375 faecal samples were randomly collected. Then, the presence of parasitic infection and its intensity (mild, moderate and severe) was determined. The analysis was conducted according to the possible relationship between prevalence and intensity of infection with intrinsic variables using logistic regression methods. The eggs of Trichostrongylus axei (93.6%), Strongyle spp. (93.6%), Parascaris equorum (20.8%) and Strongyloides westeri (8.3%) larvae were identified in this study. The total prevalence rate was 93.6%.The severe infection was in the highest rate (41.9%), even for males (45.2%), young equines (51%). Total mean EPG was found to be 934.2 ± 29.6, with the highest mean for donkeys (981.2 ± 40.4), males (984.6 ± 38.1) and young equines (999 ± 84.5). Statistically, a significant relationship was seen between gender of animals and prevalence and intensity of infection (P=0.007; P=0.001, respectively), whereas there was no significant relationship between prevalence and intensity of infection and age (P=0.68; P=0.11, respectively) and species (P=0.37; P=0.09, respectively), though the prevalence rates was higher in donkeys and adults; and intensity of infection was higher in donkeys and young equines, in total. Due to very high prevalence and intensity of infection, it is necessary to pay attention to the health of equines.
Keywords: Prevalence; Intensity; Gastrointestinal Nematodes; Working Equines; Iran